La semaine annuelle de musique de Montréal sous les auspices du Delphic Study Club, 1923–1937 - Lefebvre, Marie-Thérèse (Canadian University Music Review / Revue de musique des universités canadiennes, 2001)
This study begins with an examination of the background against which was founded the annual Music-Week in Montreal (1923–1937), then presents an analysis of its system of operation, inspired by the American model created in 1920 by Charles Milton Tremaine. Information on the staff of the association, its sponsors, financial grants, concert venues, performers, repertory, and lecturers is discussed; the main points of the press reviews of the events are extracted. The anglophone-francophone cultural dualism with regard to the conception of music and of its role in education emerges clearly in the conclusion, which also highlights the active role of women in the running of organizations destined to spread music in Quebec.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

Popularité, identité et internationalisation : les phénomènes Plamondon et Dion - Oberhuber, Andrea; Poulin, Richard (Les frontières improbables de la chanson, 2001)